POLA INTERAKSI SATU ARAH PENDIDIK DAN PESERTA DIDIK DALAM PEMBENTUKAN KARAKTER ANAK PADA NOVEL TOTTO-CHAN: GADIS CILIK DI JENDELA - Rahma Nissa; Indah Muliati (As-Sulthan Journal of Education, 2026)
This study examines the one-way interaction pattern between educators and students in the formation of children’s character in the novel Totto-Chan: The Little Girl at the Window. This research study is limited to the form of one-way communication between educators and students in the formation of children’s characters in the novel Totto-Chan: The Little Girl in the Window. This study aims to describe the characters formed through one-way interaction patterns between educators and students in the novel Totto-Chan: The Little Girl in the Window. This research is a qualitative study with a content analysis approach and is descriptive. The results show that one-way interaction patterns in the novel are carried out through four forms, namely commands, explanations, directions, and advice. One-way interaction patterns contribute to the formation of characters of discipline, empathy, honesty, cooperation, independence, self-confidence, respect, curiosity, responsibility, and tolerance. Thus, one-way interaction patterns delivered directly and attentively can still form effective communication that can have an impact on the formation of children’s characters.